Putin's Russia and Southeast Asia The Kremlin's Pivot to Asia and the Impact of the Russia-Ukraine War - Storey, Ian (Singapore SEAS-Yusof Ishak Institute, 2025)
In the first major study of Russia-Southeast Asia relations since the end of the Cold War, Ian Storey traces the dramatic shifts in Moscow's interests in the region under President Vladimir Putin. He skillfully assesses the long-lasting legacy of the Soviet Union, traces the evolution of Putin's foreign policy and identifies the driving forces behind the Kremlin's Pivot to Asia. With expert insights, Storey examines Russia's political, economic and military engagement with ASEAN abnd each of the eleven Southeast Asian countries over the past quarter of a century. He also delivers in-depth analysis on how Southeast Asia responded to Russia's invasion in Ukraine in 2022, and what the Russia-Ukraine War means for Moscow's great power ambitions in the region and beyond.
Includes bibliographical references (pages [468]-482) and index.
Donated by Mr. Ian Storey
Keywords: Russo-Ukrainian War -- 2014-; Southeast Asia -- Foreign relations -- Russia; Russia -- Foreign relations -- Southeast Asia; Southeast Asia -- Foreign economic relations -- Russia .; Russia -- Foreign economic relations -- Southeast Asia